Existential Chaos: A Critique of Catherine Keller’s Position Towards Creation and Divine Omnipotence - Linthicum, Emily (Lumen et Vita, 2014)
The two dominant concepts Catherine Keller examines in her study of creatio ex profundis, creation out of chaos, are the feminine tehomic language and refutation of divine omnipotence. She studies both these concepts through a feminist lens as well as with an overarching question as to why creatio ex nihilo, creation from nothing, has commandeered the thought behind Genesis exegesis and creation theology. Using various literary styles, both religious and secular, Keller attempts to deconstruct creation out of nothing and argue how a theology of becoming is more appropriate given the language of Genesis and creation as a whole. Rather than merely substitute the present masculine understandings of God and creation with the feminine, she persuades for a return to the foundation of tehomic language in an effort to reconstruct the negative feminine connotations of chaos and support a theology of becoming without a “divine dominology.” The purpose of this paper is to offer an examination of Keller’s text and counterarguments to her understanding of creatio ex nihilo and ex profundis. There are various examples of male dominant thought in theology throughout history; however, divine omnipotence, both in general and as associated with creation theology, is not an affront to the feminine and creatio ex profundis. Keller’s fault does not lie in the notion of creatio ex profundis and its validity; rather, her argument concerning the domineering power of divine omnipotence and its association with creatio ex nihilo remains insufficient.